Newborn screening for genetic disorders: Current status and prospects for the future - Si Ding; Lianshu Han (Wiley, 2022)
ABSTRACT Newborn screening (NBS) is a public health service aimed at identifying infants with severe genetic disorders, thus providing effective treatment early enough to prevent or ameliorate the onset of symptoms. Current NBS uses biochemical analysis of dried blood spots, predominately with time‐resolved fluorescence immunoassay and tandem mass spectrometry, which produces some false positives and false negatives. The application of enzymatic activity‐based testing technology provides a reliable screening method for some disorders. Genetic testing is now commonly used for secondary or confirmatory testing after a positive result in some NBS programs. Recently, next‐generation sequencing (NGS) has emerged as a robust tool that enables large panels of genes to be scanned together rapidly. Rapid advances in NGS emphasize the potential for genomic sequencing to improve NBS programs. However, some challenges still remain and require solution before this is applied for population screening.